Students’ Attitude Toward Active Learning in Health Science Education: The Good, the Challenges, and the Educational Field Differences - Leksuwankun, Surachai; Bunnag, Suwiwat; Namasondhi, Amornrut; Pongpitakmetha, Thanakit; Ketchart, Wannarasmi; Wangsaturaka, Danai; Itthipanichpong, Chandhanee (Frontiers in Education, 2022)
Active learning is an important shift in pedagogical paradigms in recent decades. Previous studies establish many benefits from this learning strategy. However, an implementation is challenging. This study aimed to clarify an explanation of the benefits and challenges of active learning from various educational field students’ perspectives. This study was conducted in a general education course at Chulalongkorn University. Underpinning with a mixed-method study, 22 undergraduates were interviewed in a focus group study. Results were analyzed with deductive thematic analysis and contributed to 23 items in close-ended questionnaires for a cross-sectional quantitative survey study. Notably, 222 undergraduates revealed their attitude toward active learning including benefits and challenges. Quantitative data were analyzed with analytical statistics including the Mann-Whitney U test, and these results are supported by thick descriptions derived from the qualitative data. This study revealed students’ attitude in benefits of active learning dividing into cognitive domain, student efficacy, and 21st century skills, and also challenges of active learning in teachers, students, and pedagogical aspects. Health science undergraduates tended to agree that active learning exposure enhances effective active learning than non-health science undergraduates (U = 2843, p = 0.029). An educational theory is also discussed with these results, and an educational implication to achieve an effective learning strategy is presented in this study.